The Influence of Raw Material Costs, Direct Labor Costs, Overhead Costs, and Operational Costs on Sales Turnover - Afwika, Rahmawani; Anggraini, Tuti; Nasution, Yenni Samri Juliati (Journal La Sociale, 2025)
The research conducted intends to identify the effect of raw material costs, direct labor costs, indirect costs, and operational costs on sales turnover at the Upik family chip factory, both individually and as a whole. The method applied is a quantitative approach through a causal associative type of study, using secondary data. The resulting research indicates that simultaneously, the variables of raw material costs, labor costs, overhead costs, and operational costs have a significant influence on sales turnover as the dependent variable. Partially, the variables of raw material cost, overhead cost, and operational cost are proven to be able to significantly influence sales, while direct labor cost does not show a significant influence